Pengaruh Product Involvement, Milk Knowledge Dan Perceived Value Terhadap Purchase Intention ( Kasus : Produk Susu Ultramilk) - Chairy, Ricky dan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
This study aimed to know the effect of the product involvement, product knowledge and perceived value that consumer’s have towards purchase intention on Ultramilk products with product knowledge and perceived value towards purchase intention as the mediating variable. The variables used were product involvement, produk knowledge, perceived value and purchase intention. This study uses quantitative method. The data collection technique use online questionnaires distributed to 100 respondents namely consumers that have drink Ultramilk milk products before with non probability sampling method. The analysis method that used in this study was pls-sem (structural equation modelling). The result showed that product involvement positively and significantly affect to product knowledge,perceived value and purchase intention directly and perceived value have positively and significantly affect to purchase intention but for produk knowledge no have significantly affect to purchase intention but product knowledge have significantly affect to perceived value which perceived value have positive affect to purchase intention.